2022
DOI: 10.1111/cga.12466
|View full text |Cite
|
Sign up to set email alerts
|

A predicting model of child‐bearing‐aged women’ spontaneous abortion by co‐infections of TORCH and reproductive tract

Abstract: To develop a predicting model of child‐bearing‐aged women’ spontaneous abortion (SA) by co‐infections of TORCH and reproductive tract, in order to provide a reference tool for accurately predicting the risk of SA and guide the early prevention, diagnosis and treatment of SA. A prospective cohort study was designed based on 218 958 child‐bearing‐aged women following up in Hebei province in China from 2010 to 2017. Multivariable logistic regression analysis was used to select candidate predictive variables. Fish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 79 publications
0
1
0
Order By: Relevance
“…Early diagnosis of ESA can improve the management of pregnant women, reduce the risk of miscarriage, prevent related complications, and carefully monitor ESA and pregnancy progression. 11 , 12 Serum β‐Human Chorionic Gonadotropin (β‐HCG) has been widely used in early pregnancy assessment, 13 However, it has been suggested that serum β-hCG is moderately predictive of ESA (AUC = 0.748, specificity = 71.13 %, sensitivity = 67.71 %). 14 Therefore, there is an urgent need to find better diagnostic biomarkers associated with this pregnancy complication.…”
Section: Introductionmentioning
confidence: 99%
“…Early diagnosis of ESA can improve the management of pregnant women, reduce the risk of miscarriage, prevent related complications, and carefully monitor ESA and pregnancy progression. 11 , 12 Serum β‐Human Chorionic Gonadotropin (β‐HCG) has been widely used in early pregnancy assessment, 13 However, it has been suggested that serum β-hCG is moderately predictive of ESA (AUC = 0.748, specificity = 71.13 %, sensitivity = 67.71 %). 14 Therefore, there is an urgent need to find better diagnostic biomarkers associated with this pregnancy complication.…”
Section: Introductionmentioning
confidence: 99%